2015
DOI: 10.4172/2155-6113.1000471
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Health Locus of Control and Risky Sexual Behaviors among Nigerian Adolescents

Abstract: HIV/AIDS knowledge has been rated as the most important factor for HIV prevention. However, studies have also shown that knowledge alone does not always translate into reduced risky sexual behavior (RSB). Health locus of control (HLC) categorized as perceived control over health status (internal locus of control) or attribution of health status to chance or fate (external health locus of control) is a psychological construct that has been shown to impact health outcomes including RSB. This study thus investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…We found that adolescents with high levels of CSB symptoms (classified as the CSB group), in comparison to sexual fantasizers and abstaining adolescents, are characterized by an external locus of control, anxious attachment, greater loneliness, higher frequency of PU, and more sex-related online activities. While some of our findings are in keeping with previous studies such as the links between CSB, loneliness (Dhuffar et al., 2015), and external locus of control (Pharr et al., 2015), the current research also yielded several unique and novel results.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We found that adolescents with high levels of CSB symptoms (classified as the CSB group), in comparison to sexual fantasizers and abstaining adolescents, are characterized by an external locus of control, anxious attachment, greater loneliness, higher frequency of PU, and more sex-related online activities. While some of our findings are in keeping with previous studies such as the links between CSB, loneliness (Dhuffar et al., 2015), and external locus of control (Pharr et al., 2015), the current research also yielded several unique and novel results.…”
Section: Discussionsupporting
confidence: 88%
“…This perception distinguishes them from sexual fantasizers, who do not worry about the consequences of their sexual thoughts, and from abstaining adolescents who can control their sexual thoughts, and do not suffer from high negative affect. Research has indeed linked external locus of control to risky sexual behavior (Pharr et al., 2015; St. Lawrence, 1993), such as lower likelihood of wearing a condom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no statistically significant association between the closely-related assertiveness self-efficacy scale and safe-sex practice in this study; however, poor assertiveness and low perceived personal control are thought to be predictors of risky sexual behavior. 20-22 Hence, college students also need to build their self-assertiveness skills during this critical period of psychosocial development and our findings further emphasize the importance of good partner disapproval-related self-efficacy in relation to safe sexual behavior.…”
Section: Discussionmentioning
confidence: 53%
“…The extent to which HIV risk perception modifies engagement in HIV risk behaviors continues to be unclear and inconsistent (Prata, Morris, Mazive et al, 2006). HIV risk perception may not ultimately lead to reductions in high-risk behaviors, as socioeconomic, sociocultural and structural constraints represent an external locus of control that high-risk populations face, but cannot necessarily overcome (Pharr, Enejoh, Mavegam et al, 2015).…”
Section: Discussionmentioning
confidence: 99%